2014
DOI: 10.1002/chem.201404090
|View full text |Cite
|
Sign up to set email alerts
|

Potent Anticancer Activity and Possible Low Toxicity of Platinum(II) Complexes with Functionalized 1,1‐Cyclobutanedicarboxylate as a Leaving Ligand

Abstract: Two platinum(II) complexes, DN603 and DN604, were designed and prepared by using 3-oxocyclobutane-1,1-dicarboxylate as a ligand. The compounds were prepared according to the concept that incorporation of a functionalized moiety in the leaving ligand that did not affect its coordination bonding to the metal atom would play a key role in the anticancer activity of the resulting platinum complex. The newly prepared compounds were found to show potent in vitro anticancer activity comparable to cisplatin and oxalip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 40 publications
(58 reference statements)
0
22
0
Order By: Relevance
“…Materials and General Measurements. Common chemicals and solvents were purchased from Sinopharm Chemical Reagent Co.(Beijing, China) DN604 (1) and DN603 (2) were prepared as described previously (Zhao et al, 2014). Elemental analyses for C, H, and N were done on a Vario MICRO CHNOS Elemental Analyzer (Elementar, Fulda, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Materials and General Measurements. Common chemicals and solvents were purchased from Sinopharm Chemical Reagent Co.(Beijing, China) DN604 (1) and DN603 (2) were prepared as described previously (Zhao et al, 2014). Elemental analyses for C, H, and N were done on a Vario MICRO CHNOS Elemental Analyzer (Elementar, Fulda, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the leaving ligand plays a significant role in determining the toxicity and side effects of a platinum drug. With the purpose of retaining the advantage of 1,1-cyclobutanedicarboxylate as a leaving ligand and also improving the kinetic properties of the resulting platinum complexes, we have introduced a carbonyl group to the skeleton of 1,1-cyclobutanedicarboxylate, in which the functionalized moiety (carbonyl group) could achieve the desired balance between hydrophilicity and lipophilicity of the resulting platinum complex and may improve the kinetic properties as well as the DNA-binding ability of the derivatives (Zhao et al, 2014). Such platinum complexes, named DN603 and DN604 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…CasIII-La CasIII-Ea Cisplatin [34] Carboplatin [31] Lobaplatin LP-D1 [35] Lobaplatin LP-D2 [35] Dose [mg kg [8] -0.806 [8] -2.19 [51] -2.3 [51] 1.48 [56] 1.48 [56] Parameter SM54111 [36] DN604 [32] Dicycloplatin [37] LCC0601 (S,S) [38] LCC0601 (R,R) [38] Oxaliplatin [53] Dose [55] ----1.65 [51] Figure 3. Pt compounds presented in Table 3: (1) cisplatin, (2) carboplatin, (3) dicycloplatin, (4) lobaplatin LP-D1, (5) lobaplatin LP-D2, (6) SM54111, (7) LLC0601 (R,R), (8) LLC0601 (S,S), (9) DN604, and (10) oxaliplatin.…”
Section: Parametermentioning
confidence: 99%
“…[15][16][17][18] In our previous research, complexes A and B exhibited similar activity compared with cisplatin and oxaliplatin, but their toxicity against normal cells was lower than that of cisplatin and oxaliplatin. 19,20 The results indicated that both of them were promising anticancer lead compounds for further study (Fig. 1).…”
Section: Introductionmentioning
confidence: 95%
“…Molecular formulas and [M + Na] + experimental and theoretical of 1a-2b Creative Commons Attribution-NonCommercial 3.0 Unported Licence.study 19. All tumor cell lines were purchased from Hangzhou Hibio bioTech company.…”
mentioning
confidence: 99%